MASS MEDIA FRAMING ON DISASTER: CASE STUDY LANDFIRE IN SOUTH SUMATERA - Murti, Krisna; Musdalifah, Farisha Sestri; Andarinini, Rindang Senja; izzudin, muhammad (Natapraja, 2023)
Indonesia is among the nations with the highest number of natural disasters. This syndrome is aggravated by unbalanced information provided by the media. The media use framing to enforce information distribution rules, particularly in regards to forest and land fire reporting. Using a constructivist research methodology, this study argues that framing is the key to influencing public opinion towards actors who might be perceived positively or negatively. The results showed that mass media framing was divided into several themes. This framing explains how the mass media has an important role in disseminating disaster-related information to the public. Some evidence suggests that political competition among the local political elite contributes to the occurrence of forest fires, it’s also ensued in mass media in Indonesia. If the government is unable to enforce strong regulations on irresponsible parties, forest fires will persist. The mass media must exist as a tool to regulate its population so that they do not burn forests and land that is detrimental to the nation.